2014
DOI: 10.1111/aji.12298
|View full text |Cite
|
Sign up to set email alerts
|

Interleukin-18 and Interferon Gamma Levels in Preeclampsia: A Systematic Review and Meta-analysis

Abstract: This meta-analysis suggests that circulating higher IFN-γ levels may be associated with preeclampsia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 37 publications
(24 citation statements)
references
References 49 publications
(132 reference statements)
0
23
0
Order By: Relevance
“…The pro-inflammatory cytokine, interferon gamma (Ozkan et al, 2014; Yang et al, 2014) has been reported to be increased in the circulation (plasma and serum) of preeclampsia patients. Additionally, patients with temporal lobe epilepsy have also been reported to have increased levels of interferon gamma (Vieira et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…The pro-inflammatory cytokine, interferon gamma (Ozkan et al, 2014; Yang et al, 2014) has been reported to be increased in the circulation (plasma and serum) of preeclampsia patients. Additionally, patients with temporal lobe epilepsy have also been reported to have increased levels of interferon gamma (Vieira et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…In a meta-analysis of 16 studies looking at maternal plasma and serum in normal and PE pregnancies by Yang et al (Yang et al 2014), there was a significant trend in the literature for increased interferon (INF)γ levels in PE pregnancies. In 5 independent studies, however, there was no difference observed.…”
Section: Hormones Of Preeclampsia-related Endothelial Dysfunctionmentioning
confidence: 99%
“…In the recently published meta‐analysis by Yang et al, nine studies that measured IL‐18 serum levels in PE and normotensive women were included: Studies were based on third‐trimester blood samples, and MD values were not significantly different between PE and controls (95% CI: [−0.4‐0.53], I 2 = 89.1%). In the same review, another two studies assessed but not included, concluded to similar results.…”
Section: Resultsmentioning
confidence: 99%